Identifying habitat patches and potential ecological corridors for remnant Asiatic black bear ( Ursus thibetanus japonicus) populations in Japan - Doko, Tomoko; Fukui, Hiromichi; Kooiman, Andre; Toxopeus, A.G.; Ichinose, Tomohiro; Chen, Wenbo; Skidmore, A.K. (Ecological modelling, 2011)
The Japanese National Biodiversity Strategy 2010 calls for the creation of ecological networks as a biodiversity conservation policy. However, there is an obvious lack of information on the spatial distribution of many species and a lack of scientific methods for examining habitat requirements to establish the need for constructing these networks for target species. This study presents a quantitative method for assessing the need for ecological networks through modeling the potential geographic distributions of species based on a case study of local populations of Asiatic black bear ( Ursus thibetanus japonicus) in Fuji and Tanzawa, Japan. A total of 1541 point records of occurrences of Asiatic black bears and 11 potential predictors were analyzed in a GIS environment. After a predictive distributional map was obtained using the Maximum Entropy (MaxEnt) algorithm, a gap analysis was carried out and population size was estimated. Approximately 24% of the bear's predicted habitat area fell within a wildlife protection area, 2% within a nature reserve, and 37% within natural parks. Conservation forest comprised 54% of the total area of predicted habitat; of this, national forest comprised 2%, and private and communal forest comprised 37%. The total estimated Asiatic black bear population in this region was 242, with 179 individuals in the Fuji local population, 26 in the Tanzawa local population, and 37 in the corridor patch between the two local populations. Our study also found a potential corridor connecting the Fuji and Tanzawa local populations, as well as potential habitat corridors in the Fuji region containing subpopulations on Mt. Fuji (119 individuals) and Mt. Kenashi (53 individuals). An additional subpopulation on Mt. Ashitaka (7 individuals) is isolated and not fully protected by a zoning plan. Mt. Furo's subpopulation is considered to be almost extinct, although black bears were observed here until 2002 based on the report by Mochizuki et al. (2005). The total black bear population of the Fuji-Tanzawa region is considered to be “endangered”; thus, an adequate population size might be difficult to maintain even if this region were to be internally connected by means of an ecological network.